(untitled) (Journal of the College of Basic Education, 2022)
The current research aims to identify: Measuring the problem solving method among university students.1 2.Find differences in the method of solving problems among university students according to sex variables a - (male - female) B - specialization (scientific – human) Measuring the cognitive anxiety of university students.3 4.Find differences in the cognitive anxiety of university students according to sex variables a - (male - female) B - specialization (scientific – human) 5.To identify the nature of the relationship between the method of problem solving and cognitive anxiety among university students. 6.To find the difference in the nature of the relationship between the method of solving the problems and the cognitive anxiety of the university students according to the sex variables (a - male - female) B - specialization (scientific - human). The research was determined by university students (first - fourth) of the University of Baghdad in the city of Baghdad for the academic year (2016-2017). To achieve the research objectives, the researcher adopted the following: 1-Building a measure of the method of solving the problems of university students according to the literature and theoretical backgrounds, the standard was finalized after completing the conditions of honesty and stability and the ability to distinguish from (35) paragraph were divided into five methods are (positive orientation problem, negative trend problem, The reckless-indifferent model, solving the rational problem) 2-The construction of the cognitive anxiety scale, where the scale is of (25) paragraphs divided in two fields in an unequal way. The statistical analysis of the scales of the scale shows that it has a statistically significant discrimination power at the level of 0,05. The psychometric properties (honesty and consistency) The researcher applied the measurements on a sample of (200) students at the University of Baghdad in Baghdad for the academic year (2015-2016) and then analyzed the data using the statistical bag for social sciences (spss) and (Microsoft Excel) 1-The students of the college with their scientific and human branches use positive methods in solving their problems. 2-There are no statistically significant differences in the method of solving problems according to gender variable (male and female) and specialization (scientific – human). 3-The students of the college branches scientific and human suffering from cognitive anxiety. 4-The absence of differences of statistical significance in the degree of cognitive anxiety according to gender (male - female) and specialization (scientific – human) 5-There is a positive relationship between the method of problem solving and knowledge anxiety. Based on these results, the research came out with a number of recommendations and suggestions.